ANALISIS STRATEGI PEDAGOGIS GURU DALAM MENUMBUHKAN BUDAYA LITERASI SISWA MADRASAH IBTIDAIYAH: SEBUAH STUDI KEPUSTAKAAN - Handayani, Sri; Umami, Mashlihatul (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2026)
Literacy culture in Madrasah Ibtidaiyah is an essential foundation for the development of students' character and cognitive skills in the dynamic digital era. This study aims to analyze various effective pedagogical strategies used by teachers in fostering literacy culture through a systematic literature review. The research method used was a literature study of twelve reputable scientific articles from the Scopus database and Sinta 2 journals in the period from 2021 to 2025. The data were analyzed using content analysis techniques to synthesize the findings in depth and objectively. The results of the study identified four main pillars of strategy: strengthening the habit formation ecosystem through teacher role modeling, integrating digital literacy and artificial intelligence, implementing adaptive teaching that prioritizes student well-being, and utilizing texts based on local wisdom. These strategies indicate a paradigm shift from merely technical reading skills to a multimodal process of meaning construction. The discussion emphasizes that a holistic approach combining psychosocial aspects with technological innovation has proven to be most effective in increasing madrasah students' interest in reading and critical thinking. In conclusion, the success of a culture of literacy is largely determined by the synergy between responsive pedagogical strategies and educators' self-efficacy.The implications of this study suggest the need to develop a more inclusive and transformative madrasah curriculum in order to realize the vision of the Golden Generation 2045. ABSTRAK Budaya literasi di Madrasah Ibtidaiyah merupakan fondasi esensial bagi pengembangan karakter dan kecakapan kognitif siswa di era digital yang dinamis. Penelitian ini bertujuan untuk menganalisis berbagai strategi pedagogis guru yang efektif dalam menumbuhkan budaya literasi melalui tinjauan literatur sistematis. Metode penelitian yang digunakan adalah studi kepustakaan terhadap dua belas artikel ilmiah bereputasi dari basis data Scopus dan jurnal Sinta 2 dalam rentang waktu 2021 hingga 2025. Data dianalisis menggunakan teknik analisis isi untuk mensintesis temuan secara mendalam dan objektif. Hasil penelitian mengidentifikasi empat pilar strategi utama: penguatan ekosistem habituasi melalui keteladanan guru, integrasi literasi digital dan kecerdasan buatan, penerapan pengajaran adaptif yang memprioritaskan kesejahteraan siswa, serta pemanfaatan teks berbasis kearifan lokal. Strategi tersebut menunjukkan pergeseran paradigma dari sekadar kecakapan teknis membaca menuju proses konstruksi makna yang multimodal. Diskusi menekankan bahwa pendekatan holistik yang menggabungkan aspek psikososial dengan inovasi teknologi terbukti paling efektif dalam meningkatkan minat baca serta nalar kritis siswa madrasah. Kesimpulannya, keberhasilan budaya literasi sangat ditentukan oleh sinergi antara strategi pedagogis yang responsif dan efikasi diri pendidik. Implikasi penelitian ini menyarankan perlunya pengembangan kurikulum madrasah yang lebih inklusif dan transformatif guna mewujudkan visi Generasi Emas 2045.